Influence of COVID-19's active cases on Malaysia's key economic performance indicators / Abd Hadi Mustaffa ...[et al.] - Mustaffa, Abd Hadi; Zainal Abidin, Nur Balqishanis; Ahmad, Noryati; Ogundare, Emmanuel Abiodun (Universiti Teknologi MARA, 2021)
The COVID-19 outbreak was a rare and unprecedented phenomenon. Hence, the pandemic forces the world economy to react unpredictably. Governments worldwide have undertaken several precautions, including social distance measures, public awareness programs, policies on testing and quarantine, and financial aid packages. Using endogenous growth theory, this paper examines the impact of COVID-19 towards Malaysia key economic indicator's performance using univariate regression analysis based on daily time series data from 1 January 2020 to 30 September 2020. Besides, this paper is also forecasting the upcoming three months of Malaysia's key economic indicator performance from October to December 2020, by using linear trend forecasting model. The results indicate that COVID-19 significantly impacted the unemployment rate, gross domestic product (GDP), consumer price index (CPI), foreign exchange rate (FOREX), and stock market index performance in Malaysia. The results of projecting the upcoming three months trends were forecasted to increase unemployment, GDP, FOREX, and stock market index performance. Instead, the CPI is expected to decrease. Furthermore, this paper provides four contributions in the later section.